2017
DOI: 10.1371/journal.pntd.0005407
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cholera outbreaks and socio-economic characteristics of the communities in the fishing villages of Uganda: 2011-2015

Abstract: BackgroundThe communities in fishing villages in the Great Lakes Region of Africa and particularly in Uganda experience recurrent cholera outbreaks that lead to considerable mortality and morbidity. We evaluated cholera epidemiology and population characteristics in the fishing villages of Uganda to better target prevention and control interventions of cholera and contribute to its elimination from those communities.Methodology/Principal findingsWe conducted a prospective study between 2011–15 in fishing villa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 22 publications
5
63
0
Order By: Relevance
“…In an outbreak investigation of cholera in western Kenya, 2015 by Oyugi, observed that 69% (36) reported having suffered abdominal pain and fever while 12%. 8 Date-wise analysis of number of cases revealed that number of cases were at its peak followed by sharp fall on subsequent days, this finding supports point source nature of the epidemic with single incubation period.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…In an outbreak investigation of cholera in western Kenya, 2015 by Oyugi, observed that 69% (36) reported having suffered abdominal pain and fever while 12%. 8 Date-wise analysis of number of cases revealed that number of cases were at its peak followed by sharp fall on subsequent days, this finding supports point source nature of the epidemic with single incubation period.…”
Section: Resultssupporting
confidence: 52%
“…In an outbreak investigation of cholera in western Kenya, 2015 by Oyugi, it was observed that females constituted 61% (95/156) of all participants, The ages of 939 (96%) cases were recorded and their median age was 16 years (Range <1 to 100 years). 8 The age group 6-15 years had the highest number of cases at 27% (256), while the least cases were in the age group <2 years at 7% (72).…”
Section: Resultsmentioning
confidence: 96%
“…vulnerable due to conflict, food insecurity, poor socio-economic status, environmental conditions, inadequate access to safe water and sanitation, and limited access to health services [31]. Furthermore, the ongoing and prolonged humanitarian crises in these countries drive population movements, thus facilitating the spread of the disease within and between countries as well as causing extensive deterioration of health, transport, shelter and water, sanitation and hygiene services [32,33].…”
Section: Epidemiology and Infectionmentioning
confidence: 99%
“…One practical implementation of the "Mass and Maintain" vaccination strategy in a camp setting can include a one-time mass vaccination campaign followed by routine vaccination of new members of the population, such as births and new entries. Population sub-groups with high vulnerability and mobility, such as coastal fishing communities, [41] may also benefit from the "Mass and Maintain" vaccination strategy targeted at seasonal influxes of migrants such as new fishermen. In an urban or open population, such as Dhaka or Calcutta, routine identification of new members becomes more challenging, but performance of the WHO Expanded Programme on Immunization in cholera endemic regions like Bangladesh are promising.…”
Section: Discussionmentioning
confidence: 99%